Penyusunan Modul EAP Terintegrasi Teknik Sketchnoting Ruang Untuk Meningkatkan Kemampuan Note-Taking Pada IELTS Listening - Margaret Stevani; Evi Martiningsih; Alexander Adrian Saragi; Fitri Rahmawati Nasution; Nurfaizah Marwan (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program developed and implemen ted an English for Academic Purposes (EAP) module integrated with spatial visual note-taking techniques to improve participants’ note-taking skills in the IELTS Listening test. The program targeted final-year students and alumni from the Departments of Architecture and English Language Education who were preparing for higher educat ion and scholarship opportunities at English Village Pare, Kediri. The program employed participatory training, project-based learni ng, & experiential learning through needs assessment, module develo pment, workshops, guided practice, and evaluation. The module was designed based on dual coding theory, cognitive load theory, and the visual note-taking framework. The implementation results demonstra ted improvements in participants’ listening comprehension, keyword identification, paraphrase recognition, visual organization of notes, and adherence to IELTS answer-writing conventions. This program produced an innovative EAP learning module that effectively, contextually, and sustainably supports IELTS Listening preparation.